Customers’ satisfaction on the quality of e-commerce / Hanitahaiza Hairuddin, Sharidatul Akma Abu Seman and Noorizan Mohamad Mozie - Hairuddin, Hanitahaiza; Abu Seman, Sharidatul Akma; Mohamad Mozie, Noorizan (Universiti Teknologi MARA, Shah Alam, 2019)
As an important profit driver for business, e-commerce gives various opportunities to small and huge companies to sustain. Customer will visit e-commerce repeatedly when they feel satisfy with e-commerce services. Hence, this study aims to investigate the impacts of service quality on e-commerce context. Information quality, e-service quality, security and usefulness were predicted to have positive relationship with the customers’ satisfaction. Using purposive sampling techniques, 388 questionnaires were collected from the customers who had experienced in using Lazada and Shopee e-commerce website. PLS-SEM was used to analyse the collected data and test the proposed research hypotheses. The results indicate that information quality, e-service quality and security have positive relationship with user satisfaction, while usefulness is not significant. This finding could be used as a guideline for the companies to improve their e-commerce services.